ANALISIS KUALITAS LAYANAN DAN HARGA TERHADAP KEPUASAN PENGGUNA KARTU TELKOMSEL DI KOTA BATAM - Yopi; Simanjuntak, Jackhon Pahala (Jurnal PROFITA : Akuntansi dan Manajemen, 2024)
There is a fairly important problem in the Telkomsel company, namely experiencing a decline in customers, there are various causes of customer decline such as the form of service quality, and price. The purpose of this study is to see the influence of service quality and price both partially and simultaneously on customer satisfaction. The data source in this study is primary data, the data collection method uses google form, research data analysis uses the SPSS 26 assistance program. The tests carried out are classical assumption tests, multiple linear regression and hypothesis testing with t-tests and f-tests. The sampling method used in this study is the purposive sampling method with a total of 104 people. The results of the study partially show the conclusion that service quality affects the satisfaction of Telkomsel card users, and price affects the satisfaction of Telkomsel card users, simultaneously Service quality, and price affect the satisfaction of Telkomsel card users.